Central banks and financial inclusion - Peter J. Morgan (Asia-Pacific Sustainable Development Journal, 2022)
Central banks can address barriers to financial inclusion in multiple ways, including regulations regarding banks and non-bank institutions, identity and know-your-client (KYC) rules, support for innovative financial products, and support for innovative financial technology (fintech). At the same time, central banks must weigh the trade-offs between financial inclusion, financial innovation and financial stability. The present paper contains a survey the policies of central banks and other financial regulators in a number of emerging Asian economies to promote financial inclusion. It serves to identify successful experiences and important lessons, and it provides a review of policies central banks adopted during the COVID-19 pandemic.